SUPERVISI AKADEMIK DAN KOMPETENSI PEDAGOGIK SEBAGAI DETERMINAN KINERJA GURU - Ika Kusuma Wardani; Misykat Malik Ibrahim; Baharuddin Baharuddin; Danial Rahman (Manajemen Pendidikan, 2022)
This article aims to examine the impact of academic supervision and pedagogic competence on teacher performance at State Junior High Schools in Ulaweng District, Bone Regency. This type of research is ex-post facto research with a positivistic-quantitative approach. Respondents in this study were 56 teachers at State Junior High Schools in Ulaweng District, Bone Regency as a whole through a saturated sample. The data collection method used is a questionnaire. Questionnaires were distributed to respondents and then analyzed through inferential statistics using multiple linear regression. The results of this study prove that: Academic supervision partially has a positive and significant effect on teacher performance by 12.8%. Pedagogic competence partially has a positive and significant effect on teacher performance by 10.9%. Simultaneously, academic supervision and pedagogic competence have a positive and significant effect on teacher performance by 23.7% at State Junior High Schools in Ulaweng District, Bone Regency. This indicates that the better the implementation of academic supervision and pedagogic competence, the higher the performance of State Junior High School teachers in Ulaweng District, Bone Regency.